Close to Home: Introductory Thoughts on the Emergence of Regional Human Rights Systems - Zombory, Katarzyna (Regional Human Rights Protection Systems Outside Europe, 2026)
This paper examines the development of universal and regional human rights systems as constituent elements of the international human rights architecture. It demonstrates how the creation of the universal human rights framework under the auspices of the United Nations, particularly its protracted formation, ideological compromises, and limited enforcement mechanisms, gave rise to the emergence of regional human rights systems. While grounded in the principles of the Universal Declaration of Human Rights, regional systems in the Americas, Europe, and Africa have adapted universal norms to distinct historical, cultural, and socio-economic contexts and have introduced judicial enforcement mechanisms. The paper argues that regional human rights systems do not undermine universality but instead operationalise it by translating the universally shared human rights framework into local contexts.Keywords: Universal Declaration of Human Rights, regional human rights systems, Inter-American system of human rights, African system of human rights, Asian perspective on human rights